Cost-effectiveness analysis of sequential biologic therapy with ixekizumab versus secukinumab as first-line treatment of moderate-to-severe psoriasis in the UK. (3rd August 2018) - Johansson, Erin Colleen; Hartz, Susanne; Kiri, Sandeep Himatlal; Kumar, Gayathri; Svedbom, Axel
Abstract: Aims: Patients with psoriasis often undergo treatment with a sequence of biologic agents because of poor/loss of response to initial therapy. With the availability of newer agents like ixekizumab and secukinumab, there is a need for cost-effectiveness analyses to better reflect current clinical practice. This study aimed to assess the cost-effectiveness of a sequence of biologic therapies containing first-line ixekizumab vs first-line secukinumab in patients with moderate-to-severe plaque psoriasis in the UK. Materials and methods: A Markov model with a lifetime horizon was developed to compare the cost-effectiveness of ixekizumab and secukinumab treatment sequences: ixekizumab → ustekinumab → infliximab → best supportive care (BSC) vs secukinumab → ustekinumab → infliximab → BSC. The model used monthly cycles, and included four health states: trial period, treatment maintenance, BSC, and death. At the end of the trial period, responders transitioned to maintenance therapy; non-responders transitioned to the next biologic in the sequence. An annual discontinuation rate of 20% was assumed for maintenance therapy. Results: The ixekizumab sequence provided cost savings of £898 (£176, 203 vs 177, 101) [year 2015 values] and gained 0.03 more quality-adjusted life-years (QALYs: 1.45 vs 1.42) vs the secukinumab sequence over the lifetime horizon. Probabilistic sensitivity analysis showed an 89.8% likelihood that the ixekizumab sequence would be cost-effective at a threshold of £20, 000 per QALY gained. Limitations: The analysis used list prices for drugs rather than confidential, preferentially priced Patient Access Scheme costs. In addition, efficacy input data were based on a network meta-analysis, as there were no head-to-head trials comparing ixekizumab and secukinumab. Conclusion: First-line treatment with ixekizumab as part of a specific sequential biologic therapy for moderate-to-severe plaque psoriasis in the UK provided slight advantages in cost savings and QALYs gained over a similar treatment sequence initiated with secukinumab. In view of the small magnitude of these differences, factors such as patient preferences (e.g. for number of injections) and long-term safety (e.g. related to time on the market) may also be important for clinical decision-making.